Meningkatkan Hasil Belajar Bahasa Indonesia Menggunakan Media Pembelajaran Berbasis Digital Siswa Kelas 1 MIN 7 Seluma - Resma Neli; Reni Kusmiarti; Eli Rustinar (JURNAL ILMU PENDIDIKAN, 2025)
This study aims to improve the Indonesian language learning outcomes of first-grade students at MIN 7 Seluma through the use of digital-based learning media. The background of this research is the low student achievement caused by conventional learning methods that are less engaging. This research employs a Classroom Action Research (CAR) approach conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects of this study were 24 first-grade students of MIN 7 Seluma. Data were collected through observation, interviews, written tests (pretest and posttest), and documentation. The data were analyzed using descriptive qualitative and quantitative methods by comparing the results of the pre-cycle, cycle I, and cycle II. The findings show an improvement in students’ average scores from 55.4 in the pre-cycle to 78.5 in cycle I, and further increased to 85.4 in cycle II. Students’ activeness also improved in each cycle, as indicated by higher enthusiasm, focus, and participation in learning activities. Therefore, the use of digital-based learning media is proven to be effective in improving Indonesian language learning outcomes among first-grade students at MIN 7 Seluma.